Main bearing support investigation - A comparison of wear and friction losses for different design proposals - Gynning Olofsson, Tim (My University, 2017)
Volvo Car Corporation uses a new generation of four cylinder inline engines in their automobiles. The engine family is known as Volvo Engine Architecture and the differences between the different engines are the different power outputs made possible with different engine boosts. The VEA engines utilise a bedplate design for their engines where the main bearing supports are casted into the bedplate. For the high performance engines the main bearing supports need to be sprayed with an aluminium alloy to get a strong bonding with the bedplate. The spraying is, however, expensive and an alternative solution is sought. Four design proposals, which are based on the current design of the main bearing supports, were proposed. These design proposals does not use any of the sprayed aluminium alloy material. Instead they have been designed with the goal of getting a mechanical bonding, instead of the chemical bonding that the aluminium alloy coating provides. The design proposals were evaluated by static simulations and dynamic simulations to investigate the influence on the main bearings in terms of: • radial deformations of the main bearing profiles, • total pressure and asperity contact pressure and • friction losses. The contact behaviour between the bedplate and the main bearing supports, for the different design proposals, at high temperature were also investigated. The results from the simulations were compared to results from earlier work on the sprayed main bearing supports. None of the design proposals generally provided lower friction losses compared to the sprayed main bearing support. The differences in friction loss should also by weighed against the potential cost saving, which is a question for VCC. The sprayed main bearing supports showed in general higher asperity contact pressure compared to the design proposals. Most of the bonding between the bedplate and the main bearing supports occurred on the top surfaces and the sides of the main bearing supports for the different design proposals. An investigation of getting fatigue failure in the bedplate should also be considered, if VCC should proceed with one or more of the design proposals. Keywords:Aluminium alloy, Asperity contact pressure, Bedplate, Bonding, Friction losses, Main bearings, Main bearing supports, Volvo Engine Architecture.
Keywords: Transport; Teknisk mekanik; Transport; Applied Mechanics